The Effect of Teacher Competence and Student Motivation on Learning Outcomes for Students - Marlina, Devi; Lian, Bukman; Eddy, Syaiful (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
The goal of this research is to see the impact of teacher competence and student motivation on the results of student learning. The unsatisfactory outcomes of student learning at SD Negeri 14 Kayuagung inspired this. An explanatory approach with data survey techniques by questionnaires is the analysis method used. The study sample was 246 Kayuagung grade 2 to 6 SDN 14 students. The instrument was tested using a scale from Likert. Path analysis is the data analysis methodology used. Random sampling was used in the sampling method. The results of the study show that: (1) In general, the definition of teacher competence, which is pedagogical competence, affects learning outcomes in the low category of teacher competence perceived by students. (2) The motivation of students to learn is still in the low range, not ideal for excitement and ability to learn. (3) Some students also have scores below KKM and need care from the teacher and the growth of the school's academic potential.